2012
DOI: 10.3109/10826084.2011.644843
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use, Daily Hassles, and Religious Coping Among Students at a Religiously Affiliated College

Abstract: This study found that among female college students, the relationship between daily hassles stress and alcohol use weakened with increased participation in religious coping. This finding suggests that religious coping may protect against alcohol use among female college students. The results of this study also suggest that it may be important for university-based treatment and prevention practitioners to assess involvement in religious coping practices and to include such practices in the treatment planning pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
1
12
2
Order By: Relevance
“…While the present study revealed that females do utilize positive religious coping more than males, the significant inverse relationship between positive religious coping and substance use was not moderated by sex. These findings somewhat contradict previous studies that have found that positive religious coping moderates the relationship between negative psychological factors and substance use only for females (Horton and Loukas 2013;Stoltzfus and Farkas 2012). While we cannot make firm conclusions about causality, the findings from the present study suggest that positive religious coping may provide a sense of hope and comfort for all individuals, irrespective of sex, and these psychological benefits may help deter an individual from using substances to cope with difficult life situations.…”
Section: Discussioncontrasting
confidence: 83%
“…While the present study revealed that females do utilize positive religious coping more than males, the significant inverse relationship between positive religious coping and substance use was not moderated by sex. These findings somewhat contradict previous studies that have found that positive religious coping moderates the relationship between negative psychological factors and substance use only for females (Horton and Loukas 2013;Stoltzfus and Farkas 2012). While we cannot make firm conclusions about causality, the findings from the present study suggest that positive religious coping may provide a sense of hope and comfort for all individuals, irrespective of sex, and these psychological benefits may help deter an individual from using substances to cope with difficult life situations.…”
Section: Discussioncontrasting
confidence: 83%
“…Higher scores indicate greater experiences with negative life events. The ICSRLE has evidenced good internal consistency (α = .91; Stoltzfus & Farkas, ) and excellent construct validity with other measures of negative life events (Kohn et al, ). In the current study, the internal consistency scores for the ICSRLE in first administration (α = .94) and second administration (α = .95) were excellent.…”
Section: Methodsmentioning
confidence: 96%
“…Positive religious coping is characterized as an adaptive coping strategy that includes: (a) religious forgiveness, (b) seeking spiritual support, (c) reframing of stressful event to view it as a potentially beneficial opportunity for growth and learning, and (d) finding meaning in a negative situation through spiritual connectedness with a higher power (Ano & Vasconcelles, 2005; Hill & Pargament, 2008; Pargament, Smith, Koenig, & Perez, 1998). Positive religious coping is associated with improved physical and mental health outcomes including decreased alcohol use (Ano & Vasconcelles, 2005; Stoltzfus & Farkas, 2012). …”
Section: Introductionmentioning
confidence: 99%